From Chain Growth to Step Growth Polymerization of Photoreactive Poly‐ε‐Caprolactone: The Network Topology of Bioresorbable Networks as Tool in Tissue Engineering. (18th February 2022) - Thijssen, Quinten; Parmentier, Laurens; Augustyniak, Edyta; Mouthuy, Pierre‐Alexis; Van Vlierberghe, Sandra
Abstract: Control of the network topology by selection of an appropriate cross‐linking chemistry is introduced as a new strategy to improve the elasticity and toughness of bioresorbable networks. The development of novel photocross‐linkable and bioresorbable oligomers is essential for the application of light‐based 3D‐printing techniques in the context of tissue engineering. Although light‐based 3D‐printing techniques are characterized by an increased resolution and manufacturing speed as compared to extrusion‐based 3D‐printing, their application remains limited. Via chemical modification, poly‐ε‐caprolactone (PCL) is functionalized with photoreactive end groups such as acrylates, alkenes, and alkynes. Based on these precursors, networks with different topologies are designed via chain growth polymerization, step growth polymerization, or a combination thereof. The influence of the network topology and the concomitant cross‐linking chemistry on the thermal, mechanical, and biological properties are elucidated together with their applicability in digital light processing (DLP). Photocross‐linkable PCL with an elongation at break of 736.3 ± 47% and an ultimate strength of 21.3 ± 0.8 MPa is realized, which is approximately tenfold higher compared to the current state‐of‐the‐art. Finally, extremely elastic DLP‐printed dog bones are developed which can fully retrieve their initial length upon stress relieve at an elongation of 1000%. Abstract : Control of the network topology via cross‐linking chemistry is introduced as a new strategy to fine‐tune bioresorbable photocrosslinked poly‐ε‐caprolactone (PCL) networks. Photocross‐linked PCL networks obtained via chain growth polymerization, step growth polymerization, and a combination thereof are reported and the influence on the mechanical, thermal, and biological properties as well as their digital light processing processability is elucidated.